Avian Leukosis: Will We Be Able to Get Rid of It? - Sergio Fandiño; Esperanza Gomez-Lucia; Laura Benítez; Ana Doménech (Animals, 2023)
Avian leukosis viruses (ALVs) have been virtually eradicated from commercial poultry. However, some niches remain as pockets from which this group of viruses may reemerge and induce economic losses. Such is the case of fancy, hobby, backyard chickens and indigenous or native breeds, which are not as strictly inspected as commercial poultry and which have been found to harbor ALVs. In addition, the genome of both poultry and of several gamebird species contain endogenous retroviral sequences. Circumstances that support keeping up surveillance include the detection of several ALV natural recombinants between exogenous and endogenous ALV-related sequences which, combined with the well-known ability of retroviruses to mutate, facilitate the emergence of escape mutants. The subgroup most prevalent nowadays, ALV-J, has emerged as a multi-recombinant which uses a different receptor from the previously known subgroups, greatly increasing its cell tropism and pathogenicity and making it more transmissible. In this review we describe the ALVs, their different subgroups and which receptor they use to infect the cell, their routes of transmission and their presence in different bird collectivities, and the immune response against them. We analyze the different systems to control them, from vaccination to the progress made editing the bird genome to generate mutated ALV receptors or selecting certain haplotypes.